P46 ARTERIAL STIFFNESS IN RELATION TO BIRTH CHARACTERISTICS IN THE JAMAICAN 1986 BIRTH COHORT - Nadia Bennett; Trevor Ferguson; Novie Younger-Coleman; Marshall Tulloch-Reid; Renee Walters; Amanda Rousseau; Janeil Williams; Seeromanie Harding; J. Kennedy Cruickshank; Rainford Wilks (Artery Research, 2017)
Background: We tested the association between birthweight and arterial stiffness measured by aortic pulse wave velocity (PWV) and cardio-ankle vascular index (CAVI) in a birth cohort of 30 year old Jamaicans. Methods: Participants were from the 1986 Jamaica Birth Cohort. Arterial stiffness was measured as PWV using Arteriograph 24hTM and CAVI with VaSeraTM devices. Current anthropometry (height, weight, waist and hip circumference), and brachial blood pressure measures were linked to birthweight and other early life markers of CVD risk (birth-length and maternal height). Linear regression models were used for analysis. Results: Analyses included 235 participants 44% male, with mean±SD age 29.8±0.7years, birthweight 3.1±0.0kg, PWV 6.3±0.1m/s and CAVI 6.3±0.1. Bivariate models showed men had higher arterial stiffness (p < 0.001). Maternal height (p = 0.031), waist/hip ratio (p = 0.019), BMI (p = <0.001) and blood pressure (systolic and diastolic) (p < 0.001) were associated with PWV, but only BMI (p < 0.001) was associated with CAVI. There was no association between birthweight and PWV or CAVI, p = 0.38 and p = 0.41 respectively. In multivariable models, associations between birthweight and PWV and CAVI did not change after controlling for gender, BMI, and SBP. Positive associations (coef±SE) between PWV and BMI (0.03±0.01 p = <0.01) and SBP (0.03±0.01 p = 0.001) remained significant; as did the negative associations for BMI and CAVI (−0.04±0.01 p < 0.001). Conclusion: Men had higher arterial stiffness even when controlling for blood pressure and the associations of blood pressure and BMI with PWV were positive whereas and BMI with CAVI was negative. Neither arterial stiffness measure was associated with birthweight.